2021
DOI: 10.1164/rccm.202103-0680le
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning–based Sleep Staging in Patients with Sleep Apnea Using a Single Mandibular Movement Signal

Abstract: Investissements d'avenir" program (ANR-15-IDEX-02) and the "e-health and integrated care and trajectories medicine and MIAI artificial intelligence" Chairs of excellence from the Grenoble Alpes University Foundation. This work has been partially supported by MIAI @ Grenoble Alpes, (ANR-19-P3IA-0003). N-N.L-D is an employee of Sunrise. The devices used in the study were provided by Sunrise, Namur, Belgium. Running head Mandibular jaw movements for automated sleep staging Subject category list: 15.10 This articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Our results show that, for patients at OSA risk and without an OSA diagnosis, the Berlin score is a simple questionnaire with a high sensitivity but a lack of specificity, and it can be easily used by dieticians at the beginning of a weight-loss program. Moreover, a new home sleep test has also been developed, and it can be repeated over the course of weight loss; this tool should be disseminated in physicians’ offices and obesity clinics in the future for the better management of OSA [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that, for patients at OSA risk and without an OSA diagnosis, the Berlin score is a simple questionnaire with a high sensitivity but a lack of specificity, and it can be easily used by dieticians at the beginning of a weight-loss program. Moreover, a new home sleep test has also been developed, and it can be repeated over the course of weight loss; this tool should be disseminated in physicians’ offices and obesity clinics in the future for the better management of OSA [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…To identify wake, the algorithm tested whether MJM signals were fast, irregular and non-predictable [ 31 ]. For the identification of arousal movements, the algorithm detected brisk MJM of large amplitude indicating the abrupt closure of the mouth characteristic of arousals [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Martinot et al (2019) and Pépin et al (2020) have shown that mandibular movements measured using midsagittal mounted magnetic sensors on the chin and the forehead, successfully differentiated obstructive and central events (Martinot et al, 2019) and when the signals were combined with machine learning could successfully discriminate controls from apnoea patients (RDI ≥ 5) with an area under the receiver operating characteristic curve (AUC-ROC) of 0.95 (Pépin et al, 2020). More recent work by the same group (Le-Dong et al, 2021) demonstrated that machine learning also enabled accurate sleep staging to be performed with an AUC for wake of 0.98, N1/N2 sleep of 0.86, N3 sleep of 0.97, and REM sleep of 0.96. Additionally, mandibular jaw movements (MJM) can be used as a surrogate measure for nocturnal respiratory effort (RE), since the slight protrusions of the mandible during sleep are reflective of respiratory drive (Martinot et al, 2022).…”
Section: Biological Signalsmentioning
confidence: 99%